The wage structure of Polish workers in Germany. - Brunow, Stephan; Miszczak, Katarzyna; Seibert, Holger; Wrona, Aleksandra (International Labour Review, 2026)
The article focuses on the wage structure of Polish workers employed in Germany, analyzing factors influencing their earnings using a large administrative dataset from 2018. It finds that Polish employees, who form the second-largest foreign workforce in Germany, generally earn less than German workers despite higher wages than in Poland, with returns to education and skills being lower for Poles. The study highlights that wages for Polish workers decrease as the concentration of Polish employees in the same occupation and region increases, indicating competition effects within this group, especially among less-skilled workers who arrived after Germany fully opened its labor market in 2012. Additionally, wages rise in regions with lower unemployment rates, suggesting that tight labor markets benefit both native and immigrant workers. The findings imply that wage adjustments may be necessary to retain Polish workers in Germany amid changing migration and labor market dynamics.